Process Quality Improvement Efforts to Reduce The Number of Cement Packing Bag Splits using Disabilities Six Sigma DMAIC - Sugiyanto, Didik; Handayani, Diah Kusuma (Teknik dan Ilmu Komputer, 2015)
ÃÂ AbstrakÃÂ Proses packing merupakan proses akhir dan bagian paling vital dalam menentukan hasil akhir produk semen, dalam hal ini produk semen dalam kemasan kantong. Mengingat pentingnya kualitas pada proses packing, maka diperlukan suatu metode pemecahan masalah untuk memperbaiki dan mengendalikan proses packing semen yang berlangsung di Departemen Packing sehingga jumlah produk cacat dapat diminimalisir. Pemecahan masalah dilakukan dengan metode Six Sigma, yang terdiri dari tahap Define, Measure, Analize, Improve, dan Control (DMAIC). Hasil penelitian dimulai dari tahap Define dimana didapatkan kantong pecah sebagai Critical to Quality (CTQ) prioritas. Pada tahap Measure diketahui level sigma bulan Januari 2014 sebesar 4,63 sigma dan pada bulan Februari 2014 sebesar 4,66 sigma, serta pada bulan maret sebesar 4,66 sigma. Kondisi proses untuk ketiga periode tersebut kurang stabil. Pada tahap Analyze diperoleh informasi bahwa faktor-faktor metode, mesin, material, lingkungan, serta manusia (pekerja) diduga sebagai penyebab ketidakstabilan proses packing. Pada tahapan Improve dan Control diberikan usulan Improve untuk sisi manajerial dan teknis, serta diberikan pula usulan Control untuk menjamin kualitas pada proses packing.ÃÂ Kata Kunci: Six Sigma, Critical to Quality (CTQ), proses packing, level sigmaÃÂ AbstractÃÂ Packing process is the final process and the most vital part in determining the final outcome of the cement product, in thisÃÂ case the cement product packed in bags. Considering the importance of the packing process, a problem solving method is necessary to improve and control the cement packing process that takes place in the Department Packing so that the number of defective products can be minimized. Troubleshooting was performed using the Six Sigma method comprising the steps of Define, Measure, Analyze, Improve, and Control (DMAIC). The study starts from the Define phase which consider the split bag as Critical to Quality (CTQ) priority. In the Measure phase, the sigma level known in January 2014 is 4.63 sigma,ÃÂ in February 2014 amounting to 4.66 and in March is 4.66 sigma. The condition of the three process is not very stable. In the Analyze phase the information obtained is that methods, machines, materials, environment, and human (labor) factors are suspected to be the cause of the packing process instability. At the stages of Improve and Control, ÃÂ Improve is proposed for the managerial and technical areas and Control is also proposed to ensure quality control in the process of packing.ÃÂ Key words: Six Sigma, Critical to Quality (CTQ), the process of packing, sigma level